Leveraging the relationship between BIM and asset management. Issue 1 (1st March 2014) - Hayes, Alan; Watts, Julian; Pocock, David; Shetty, Navil
Abstract : The purpose of this paper is to explain the mutually supportive relationship between building information modelling (BIM) and asset management. In doing so, it will enhance the ability of infrastructure owners and their suppliers to develop and implement processes, tools and collaborative working practices that optimise infrastructure asset costs and performance over the entire life cycle of assets. The paper has been produced to help mitigate the danger of treating BIM and asset management as isolated practices; reinforce the need to consider BIM implementation in the context of wider asset management policies, practices and systems and vice versa; and maximise the benefits from investments being made in the development and implementation of BIM and asset management. Asset management and BIM knowledge activities and standards have emerged in the UK construction industry as more or less parallel initiatives and have been crystallised in standards such as BS PAS 55 (Asset management – Specifications for the optimized management of physical assets) and the soon-to-be-published ISO 55000 and PAS1192-2 (Specification for information management for the capital/delivery phase of construction projects using building information modelling), respectively. This paper explains the relationship between these two disciplines and why they must be considered together if the full benefits of each are to be realised for both the asset owner and its service providers.